2022
DOI: 10.1002/bse.3290
|View full text |Cite
|
Sign up to set email alerts
|

A nonlinear relationship between corporate environmental performance and economic performance of green technology innovation: Moderating effect of government market‐based regulations

Abstract: Green technology innovation corporates can effectively coordinate the relationship between the environment and the economy, which has been an area of interest among academia and governments. To stimulate the sustainable green technology innovation of corporates, it is necessary to clarify the internal correlation among green technology innovation, environmental performance, and economic performance. Based on the information of 642 industrial corporates obtained from a field investigation in China, this article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…Enterprises fulfill social responsibilities by releasing resources related to protecting stakeholders' rights and enhancing stakeholders' well-being. To reduce the use of natural resources and avoid the supply shortage caused by resource scarcity and depletion, enterprises increase the R&D investment in green innovation technology and reduce the demand for resources through self-developed technology and equipment (Wang et al, 2021). Those enterprises fulfill their environmental responsibilities by saving resources and protecting the ecological environment.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Enterprises fulfill social responsibilities by releasing resources related to protecting stakeholders' rights and enhancing stakeholders' well-being. To reduce the use of natural resources and avoid the supply shortage caused by resource scarcity and depletion, enterprises increase the R&D investment in green innovation technology and reduce the demand for resources through self-developed technology and equipment (Wang et al, 2021). Those enterprises fulfill their environmental responsibilities by saving resources and protecting the ecological environment.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…As an important direction of technological revolution and industrial transformation, green innovation provides market demand support for technology, equipment, products, and services (Ghobakhloo et al, 2021). The application of green technology is conducive to reducing damage to the ecological environment, protecting natural resources, improving the efficiency of resource allocation, and demonstrating stronger competitiveness in sustainable development (de Jesus & Mendonça, 2018; Wang, Li, & Wang, 2022). Although the importance of green technology innovation and application at the national level is self‐evident, the original intention of enterprises to pursue profit maximization makes their attitudes towards green innovation very different from government behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are justified in predicting GPI, which generally fall into external and internal corporate governance mechanisms. Increasingly, studies have suggested that environmental regulation is the most important external mechanism in shaping GPI (Liu, 2021; Wang et al. , 2022c).…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are justified in predicting GPI, which generally fall into external and internal corporate governance mechanisms. Increasingly, studies have suggested that environmental regulation is the most important external mechanism in shaping GPI (Liu, 2021;Wang et al, 2022c). Recent Chinese research has corroborated the positive role of environmental regulations on corporate GPI and has further demonstrated its effect across other dimensions of such innovation (Wang et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%